Rancang bangun dan perekayasaan peralatan pengolahan air buangan industri penyaman kulit samak khrom - Kelompok Peneliti Pencemaran (Majalah Kulit, Karet, dan Plastik, 1984)
This paper suggested a design and prototype of waste water process equipment of chrom tanning leather industry. This prototype describes the biological treatment of leather industry effluent with B.O.D. reduction from 500 mg/1 to 30 mg/1.